PafS Containing GGDEF-Domain Regulates Life Activities of Pseudomonas glycinae MS82 - Xianyi Chen; Shaoxuan Qu; Xin Luo; Shi-En Lu; Youzhou Liu; Huiping Li; Lijuan Hou; Jinsheng Lin; Ning Jiang; Lin Ma (Microorganisms, 2022)
Cyclic dimeric guanosine monophosphate (c-di-GMP) is synthesized by diguanylate cyclase (DGC) with the GGDEF domain. As a ubiquitous bacterial second messenger, it regulates diverse life-activity phenotypes in some bacteria. Although 38 genes encoding GGDEF-domain-containing proteins have been identified in the genome of the Pseudomonas glycinae strain MS82, whether c-di-GMP functions as a facilitator or repressor of life-activity phenotypes is poorly understood. In this study, one of the 38 genes containing a GGDEF domain in MS82, PafS was investigated to explore its regulatory function in bacterial life activities. The PafS-deletion mutant ΔPafS and reversion mutant PafS-comp were constructed by the method of biparental conjugation and homologous recombination. The life activities of the mutants, such as antifungal activity, biofilm formation ability, polysaccharide content, and motor behavior, were explored. The results showed that all life-activity phenotypes were significantly reduced after knocking out PafS, whereas all were significantly restored to a similar level to that of MS82 after the complementation of PafS. These results suggested that PafS plays an important role in the regulation of a range of cellular activities by c-di-GMP in P. glycinae MS82.